Cytotoxicity of Methanol Leaf Extract of Artocarpus Altilis, Artocarpus Heterophyllus, and Artocarpus Camansi Against MCF-7 Breast Cancer Cells - Haryoto, H.; Widowati, Pratiwi (Journal of Nutraceuticals and Herbal Medicine, 2018)
Artocarpus had been used as traditional medicine for cancer, cirrhosis, malaria, hypertension, and diabetes. This research aimed to evaluate the cytotoxic activity of methanol leaf extract of Artocarpus altilis, Artocarpus heterophyllus, and Artocarpus camansi against MCF-7 breast cancer cell. The leaf extracts of Artocarpus altilis, Artocarpus heterophyllus, and Artocarpus camansi were obtained by the method of maceration with methanol. Phytochemical screening wasperformed by Thin Layer Chromatography with the use of silica GF-254 for stationary phase and ethyl acetate: n-hexane (2:8) for mobile phase. The cytotoxic test was conducted by MTT with diverse concentrations of extract, namely 500, 250, 125, 62.5, and 31.25 Î¼g/mL. The results of cytotoxic test were measured by ELISA reader. Based on phytochemical screening, tannin, and alkaloids were found in three extracts. Cytotoxic test demonstrated that those extracts had low cytotoxic activity against MCF-7 breast cancer cells, with IC50 of 120.85; 339.46 and 530.88 Î¼g/mL, respectively, for Artocarpus altilis, Artocarpus heterophyllus, and Artocarpus camansi.